Physiological Responses to Acute Stress: Hormonal and Cardiovascular Changes in Young Adults - Kamran, Jaleel; Fatima , Rida; Mehmood, Maria; Zahid, Hira; Ghulab, Usama; Hussein, Asma; Aftab, Muhammad Imran; Ali , Madiha; Habib, Bilal (Journal of Neonatal Surgery, 2025)
Background: Under stress, acute stress sets in motion many physiological changes overseen by the hypothalamic-pituitary-adrenal (HPA) axis and the autonomic nervous system (ANS). Seeing these reactions in younger people helps find early signs of stress-based illnesses. Objectves: To examine how cortisol and heart rate/blood pressure are affected by stress in healthy young people. Study Design: A Cross-sectional study. Place and Duration of study Department of Physiology, Watim Medical & Dental College, Rawat, Pakistan from Jan 2023 to Jan 2024. Methodology :A cross-sectional study was carried out with 80 students at a university who were 18 to 25 years old. People in the study completed the Trier Social Stress Test (TSST). Blood pressure, heart rate and cortisol in saliva were measured before and after each person underwent a stressful experience. Results : Increased levels of cortisol were observed after the stressor (on average 7.6 ± 2.3 µg/dL, p < 0.001) compared to pre-stress. Both systolic and diastolic pressure went up by 12% and 9%, respectively and the heart rate increased by 15 beats per minute on average (p < 0.001). Men had a stronger response of the heart; women’s cortisol levels were more variable. Conclusion: Young adults show major changes in hormonal and cardiovascular systems due to acute stress. This proves why it’s important to address stress early so health issues do not last a long time